2019
DOI: 10.1098/rsos.181769
|View full text |Cite
|
Sign up to set email alerts
|

Acute biotoxicity assessment of heavy metals in sewage sludge based on the glucose consumption ofEscherichia coli

Abstract: As a simple and feasible method for acute biotoxicity assessment, personal glucose meter (PGM) can be successfully applied in the early warning of environmental pollutants in sewage. In this paper, the acute biotoxicity of single and joint heavy metals in sewage and real sludge samples was systematically described based on the glucose metabolism of Escherichia coli (E. coli). Results indicated that the biotoxicity order of five single heavy metals in sewage was Hg2+ > As3+ > Cu2+ > Zn2+ > Cd2+. The joint heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Accordingly, we suggest that mannose could be a target sugar for EPS complexation with metals . In addition, a previous study pointed out a certain link between glucose and metal exposure, which supported the increase of glucose under the exposure of metals in this study. This finding suggests that glucose is also a potentially indictive monomer in the response of EPS to metals.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we suggest that mannose could be a target sugar for EPS complexation with metals . In addition, a previous study pointed out a certain link between glucose and metal exposure, which supported the increase of glucose under the exposure of metals in this study. This finding suggests that glucose is also a potentially indictive monomer in the response of EPS to metals.…”
Section: Resultsmentioning
confidence: 99%
“…Various model organisms are characterized by different level of sensitivity to the environmental contaminants. E. coli is considered as a sanitary indicator of environmental pollution; therefore, it was used as an experimental model in our study [34]. Both E. coli and C. albicans are present in human digestive tract, from where they may enter wastewater, SS and, subsequently, into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, organic complexes with heavy metals are less available for microorganisms and, therefore, can be less toxic, but they may also be used as carbon source necessary to bacteria and fungi growth. This process can release metals and introduce them into the cell metabolism and into the environment [34].…”
Section: Discussionmentioning
confidence: 99%
“…Using a personal glucose meter, it was found that Hg +2 had the highest toxicity, which disrupted E. coli metabolism and resulted in a higher glucose concentration. Cd +2 was found to have the lowest biotoxicity and, therefore, resulted in the lowest glucose concentration (Mi et al, 2019). Another study aimed to observe whether sludge-derived biochar, wood biochar, and raw wastewater sludge can immobilize heavy metals like Cd, Pb, and Zn.…”
Section: Metalsmentioning
confidence: 99%
“…Metabolism of glucose by E . coli was used by Mi, Tao, Zhang, and Si (2019) as a bioindicator of heavy metal toxicity in sludge samples. Using a personal glucose meter, it was found that Hg +2 had the highest toxicity, which disrupted E .…”
Section: Analysis and Quantification Of Characteristicsmentioning
confidence: 99%